PENDIDIKAN ISLAM DI ERA GLOBALISASI: PELUANG DAN TANTANGAN - Azyumardi Azra (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
AbstractEvery citizen of Indonesia has a right in order to get education service. There are some distributing and increasing programs of education accessibility for all of Indonesian citizen is done by government. Its main purpose, beside in order to realize education democracy, social fairness, and realizing the basic human values, it is also to enhance and strengthen all Indonesian citizens’ capacity in the global market competition. Today there are some citizens who are not able and have not opportunity to continue their education the higher education level because of geographic factor, economic and cultural factors.